INVESTIGASI KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI SPLDV BERBANTUAN APLIKASI GEOGEBRA - ray leonard januar; Joko Seobagyo (STKIP Andi Matappa, 2023)
The purpose of this study was to investigate students' problem-solving skills in SPLDV material assisted by the geogebra application. This research is a qualitative research with a case study approach. The sample in this study was students of class VIII at the junior high school level who were selected and could represent the case studies in this study. The method used is a seven-step case study approach, namely 1) identifying special cases in a group of students, 2) selecting several cases for the problem, 3) collecting qualitative data in the form of observation, 4) interviews and documentation, 5) analyzing data using MAXQDA, 6 ) describes the cases and themes that have been revealed, 7) compiles a chronology of cases and themes, and draws conclusions. The results of this case study research revealed that the sample of students had good problem-solving skills with the help of the Geogebra website.